The Influence of Proccessing Temperature on Morphological and Tribological Properties of Injection-Moulded Microparts. (21st May 2014) - Fischer, Christopher; Leisen, Christoph; Merken, Daniel; Jungmeier, Ariane; Drummer, Dietmar
Abstract : In conventional injection-moulding processes high flow and cooling velocities affect the morphological and tribological properties of microparts when compared to macroscopic parts. A novel mould technology with dynamic CO2 -tempering is targeted with an enhanced understanding of the temperature time behaviour of morphology during the setting phase which fundamentally dominates the structure formation. The scope of this paper is to provide an understanding of the processing temperature's influence, in this context mould temperature, on the morphological and tribological properties of injection-moulded microparts. Furthermore, the characteristics of tribological testing conditions in microparts should be identified with regard to optimized testing methods. Results indicate that the tribological properties of microparts are mainly influenced by nature of the skin near layers, which can be greatly improved through the application of mould temperatures close to the crystallisation temperature. Additionally, a tribological testing method is adapted for a correct and high solution of the running-in and stationary phase in order to identify the effects of the skin layer on the wear behaviour.